2022
DOI: 10.1016/j.jbc.2021.101480
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus cysteine protease pS273R inhibits pyroptosis by noncanonically cleaving gasdermin D

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…Our study presents clear and relevant evidence that pS273R protease acts as a sumoylation inhibitor and targets IKKε modification to interfere with the immune response. During revision of this paper, the work published by Zhao etc showed the pS273R exerts its protease activity to non-canonically cleave gasdermin D, disturb inflammasome-induced cell pyroptosis and promote ASFV replication [ 40 ]. Collectively, all these work explored different aspects of immune evasion by pS273R and broaden our understanding of immune evasion mechanism by ASFV.…”
Section: Discussionmentioning
confidence: 99%
“…Our study presents clear and relevant evidence that pS273R protease acts as a sumoylation inhibitor and targets IKKε modification to interfere with the immune response. During revision of this paper, the work published by Zhao etc showed the pS273R exerts its protease activity to non-canonically cleave gasdermin D, disturb inflammasome-induced cell pyroptosis and promote ASFV replication [ 40 ]. Collectively, all these work explored different aspects of immune evasion by pS273R and broaden our understanding of immune evasion mechanism by ASFV.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the canonical GSDMD-N 1–279 produced by caspase-1, the GSDMD-N 1–107 is unable to induce pyroptosis. Notably, pS273R further cleaves GSDMD-N 1-279 to produce GSDMD-N 1-107 , which suppresses GSDMD-N 1-279 -induced pyroptosis to promote ASFV replication ( Zhao et al., 2021 ).…”
Section: Escape From Innate Immunitymentioning
confidence: 99%
“…Thus, effective inhibition of pS273R affects ASFV particle maturation and infectivity ( Alejo et al., 2003 ). A recent article shows that pS273R inhibits ASFV infection-induced pyroptosis to regulate inflammatory responses ( Zhao et al., 2021 ). pS273R interacts with GSDMD and then cleaves GSDMD at G107–A108 to produce a shorter N-terminal fragment of GSDMD (GSDMD-N 1–107 ).…”
Section: Escape From Innate Immunitymentioning
confidence: 99%
“…Recently, Oh et al (2021) compared MA-104 to the renal-derived swine macrophages; they observed that MA-104 is less able to isolate the field virus, although both wild-type (MW039157) and cell-adapted (MW287337) ASFV genotype II strains grew efficiently in this continuous cell line [ 50 ]. This cell line was also efficiently used to study the interaction network of ASFV with host proteins [ 99 ] and to determine the mechanisms used by ASFV to evade the host innate immune responses [ 100 ].…”
Section: Monkey-derived Continuous Cell Linesmentioning
confidence: 99%